Development of a real time expert system for 11KV distribution automation - Uddin,, Md. Safi; Nor, , Khalid Mohamed; Salam,, Md. Sayeed (2006)
This paper presents an expert system (ES) to solve realtime fault identification, isolation and restoration of supply problems in low-voltage distribution networks. The ES receives real-time network status from a Supervisory Control and Data Acquisition (SCADA) system, which monitors the distribution network. The ES's basic architecture, its design and modelling as well as its integration with real-time communication to interface with the SCADA are discussed. The system has been tested with a practical network and the results of the test are presented.